The effect of compost application on physical properties of sandy soil - Aranyos, Tibor; Blaskó, Lajos; Tomócsik, Attila; Makádi, Marianna (Acta Agraria Debreceniensis, 2013)
The sewage sludge compost is suitable to improve the colloid-poor sandy soils, which are common characteristics of poor water- and nutrientholding capacity. The general characteristics of sandy soils are the light mechanical composition, the low content of humus and mineral colloids, large pore size and a bad aggregate stability. They have a poor nutrient supply capacity, due to its high porosity the organic matter is degraded very quickly to mineral colloids (Stefanovits et al., 1999).By the compost application the soil is enriched mineral and organic colloids, thereby improving the soil structure. The effect of addition of compost to soil the water- and nutrient-holding capacity and porosity could be increased and the bulk density could be decreased (Martens and Frankenberger, 1992).The aim of our experiment is to carry out physical measurements to determine the effects of compost treatment. In this study the results of the first year are presented.